Volar Subluxation of the Ulnar Head in Dorsal Translation Deformities of Distal Radius Fractures: An In Vitro Biomechanical Study. Issue 6 (June 2015) - Nishiwaki, Masao; Welsh, Mark; Gammon, Braden; Ferreira, Louis M.; Johnson, James A.; King, Graham J. W.
Abstract : Objectives: To quantify the effects of dorsal translation deformities of the distal radius with and without dorsal angulation on volar displacement of the ulnar head during simulated active forearm rotation, both with the triangular fibrocartilage complex (TFCC) intact and sectioned conditions. Methods: Eight fresh-frozen cadaveric upper extremities were mounted in an active forearm motion simulator, and distal radial deformities of 0, 5, and 10 mm of dorsal translation with 0, 10, 20, and 30 degrees of dorsal angulation were simulated. Volar displacement of the ulnar head at the distal radioulnar joint as a result of each distal radial deformity was quantified during simulated active supination. The data were collected with the TFCC intact and after sectioning the TFCC at its ulnar insertion. Results: Increasing isolated dorsal translation deformities increased volar displacement of the ulnar head when the TFCC was intact ( P < 0.001). Increasing dorsal translation combined with dorsal angulation increased volar displacement of the ulnar head compared with isolated dorsal angulation deformities ( P < 0.001). Sectioning the TFCC increased the volar displacement of the ulnar head caused by each distal radial deformity ( P = 0.001). Conclusions: These results emphasize the clinical importance of evaluating the magnitude of both dorsal translation and dorsal angulation when managing displaced distal radius fractures and malunions.